2020
DOI: 10.1182/blood.2020005590
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cell transplantation in chronic granulomatous disease: a study of 712 children and adults

Abstract: Chronic Granulomatous Disease (CGD) is a primary immunodeficiency resulting in life-threatening infections and inflammatory complications. Allogeneic hematopoietic cell transplantation (allo-HCT) can cure patients, but indication to transplant remains controversial. We performed a retrospective multicentre study on 712 patients with CGD undergoing allo-HCT transplanted in EBMT centres between 1993 and 2018. We studied 635 children (aged < 18 years) and 77 adults. Median follow-up was 45 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 30 publications
3
99
3
4
Order By: Relevance
“…Allogeneic HSCT can be curative for all forms of CGD and the development of reduced intensity conditioning protocols has led to relatively high rates of survival and correction of the immune deficiency (60). A recent retrospective review of 712 CGD patients transplanted at multiple centers over a 15 year period confirmed these observations, with median survival at 3 years of 85.7% and event-free survival of 75.8% (61). The PIDTC have reported that the presence of inflammatory bowel disease (IBD) complicating CGD did not affect transplant outcomes and IBD resolved by 2 years post-transplant in all affected (62).…”
Section: X-linked Chronic Granulomatous Diseasementioning
confidence: 93%
“…Allogeneic HSCT can be curative for all forms of CGD and the development of reduced intensity conditioning protocols has led to relatively high rates of survival and correction of the immune deficiency (60). A recent retrospective review of 712 CGD patients transplanted at multiple centers over a 15 year period confirmed these observations, with median survival at 3 years of 85.7% and event-free survival of 75.8% (61). The PIDTC have reported that the presence of inflammatory bowel disease (IBD) complicating CGD did not affect transplant outcomes and IBD resolved by 2 years post-transplant in all affected (62).…”
Section: X-linked Chronic Granulomatous Diseasementioning
confidence: 93%
“…A recently published multicentre retrospective study by the EBMT/ESID IEWP documents the largest CGD transplant cohort to date. 79 The study describes 712 patients (75% X-linked, 635 children <18 years) with CGD undergoing allogeneic HSCT between 1993 and 2018; 87% of transplants were after 2006. Many patients had significant disease before transplant, including infections (68%), colitis (24%) and liver impairment (9%).…”
Section: Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…82 Recent studies documenting medical problems in carriers of X-linked CGD 83,84 have led to recommendations not to use them as donors for CGD patients if possible. Although transplant outcomes are best in younger patients, 79,81 nevertheless, good outcomes can be demonstrated in adolescent and adult patients. An 82% survival was documented in 11 patients, age 17-28 years (median 19), all of whom had significant pre-existing infectious or inflammatory complications, using matched, family or unrelated or one antigen mismatched unrelated donors.…”
Section: Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…In adults, criteria are more difficult to apply due to higher rates of organ dysfunction and reported increased mortality from HSCT. Promising results in recent years [5–7] suggest that HSCT is safe and effective when delivered in a specialist center and should be carefully considered as a potentially curative option for younger adult CGD patients with an appropriate donor.…”
mentioning
confidence: 99%